Theories of the Family and Policy - Veronica Jacobsen; Lindy Fursman; John Bryant; Megan Claridge; Benedikte Jensen (New Zealand Government, The Treasury, 2004)
Policy interventions that affect or are mediated through the family typically assume a behavioural response. Policy analyses proceeding from different disciplinary bases may come to quite different conclusions about the effects of policies on families, depending how individuals within families behave. This paper identifies the implications of five theories of family and individual behaviour for the likely success of policy intervention. Anthropology documents not only the universality of the family, but also its many forms. Economic theory illustrates the capacity for well-intentioned policy to be thwarted by individual rationality. Evolutionary biology suggests that a number of fundamental drivers of behaviour are genetic predispositions and can be difficult to influence through policy. Sociology emphasises the role of social norms but recognises that individualism limits the influence of society generally on individual behaviour. Understanding the theories of the family emanating from different disciplines can enrich policy analysis by identifying how and why behaviour can be influenced. It also can serve to remind researchers of the resilience of the family and the limits of government intervention.
Keywords: A12; B49; D19; J12; J18; K0; R29; 330; family; kinship; family structure; family formation; family dissolution; public policy; family policy; regulation; New Zealand; Maori; History; Demography; Anthropology; Psychology; Sociology; Biology; Economics; evolution